Pengaruh Corona Virus Disease (Covid-19) Terhadap Penelantaran Anak : (Studi kasus di Desa. Kalisabuk, Kec. Kesugihan, Kab. Cilacap, Jawa Tengah) - A.Tajus Subky; Arlisa Sita Zahra (Civilia: Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2023)
The aim of this research is to thoroughly investigate the impact of the Covid-19 pandemic on child neglect using normative legal research. The approach taken is based on primary legal sources through the study of theories, concepts, principles and legal regulations. The research approach that the author uses in this research is to use data that has been collected and interview samples as is, without carrying out any analysis, to explain or provide an overview of the research subject, so that conclusions can be drawn that can be applied to the general public. What is the impact of the Covid-19 Pandemic on child neglect at home and what efforts are being made by the community to avoid child neglect at home during the Covid-19 Pandemic. Results of research on child neglect at home in obtaining educational rights. The results of observations regarding the impact are first, children play more than they study. Second, doing school assignments or homework given by the teacher becomes lazy, in fact it is the parents who do the tasks. Third, because learning online or online systems via Android cellphones, which are supposed to help people learn to do their assignments, is used as a means of playing games or is misused, as a result the learning is neglected. Fourth, the learning system is not on target like before the Covid-19 Pandemic, where before the Pandemic you could get satisfactory grades and even rankings, but because of the Pandemic your grades dropped or were less than satisfactory.